KEMAMPUAN ADAPTASI, PENGARUH PUPUK DAN KANDUNGAN GIZI BERBAGAI KULTIVAR BROKOLI (Brassica oleracea L. var. italica) INTRODUKSI DI KOPANG, LOMBOK TENGAH - Gafari, Zaenul; Kriswiyanti, Eniek; Astarini, Ida Ayu (Metamorfosa: Journal of Biological Sciences, 2015)
This research was aimed to determine adaptability of  eight introduced  broccoli cultivars in the tropical climate, the effect of fertilizers, as well as determine the content of vitamin A, C and fiber owned by the cultivar. This research was using randomized complete block design (RCBD) with two factors. The first factorsare different broccoli cultivars namely Broccoli 'Lucky', Broccoli 'B-106', Broccoli 'B-116', Broccoli 'B-112', Broccoli 'Green 2109' F1, Broccoli 'Green calabrase' and Broccoli 'Green Magic 'and Broccoli' Mujur'as a control. The second factors fertilizer of ZA, manure and urea. This research was performed in Kopang, Central Lombok, West Nusa Tenggara, for seven months from December 2014 to Juni 2015.Analysis of the nutrient content was done at the Laboratory of Analytical Chemistry, University of Mataram, Lombok. Parameters observed in this research were plant height, number and weight of leaves, and quality of curd . Data were analyzed by analysis of variance (ANOVA) if significantly different then tested further by Duncan's Multiple Range Test (DMRT) at 5% level. The results showed all the cultivars able to adapt. Broccoli 'B-106' is a cultivar that has the quality and quantity of curd most excellent and able to adapt to high temperatures. ZA fertilizer application will produce curd weight and diameter greater than that ofmanure or urea. The research also showed that cultivar B-112 has the highest content of vitamin A, B-116 has the highest vitamin C and Green 2109F1 has the highest fibers. Key word: broccoli cultivars, adaptation, heat tolerance
Keywords: broccoli cultivars, adaptation, heat tolerance